Employment Retention Policy - Fox, E.; Stafford, B. (Nottingham University, 2007)
This Report investigates the potential for a statutory model of employment retention leave. A Private Members Bill (HC Bill 2006-07) [79] currently in progress through Parliament would, if enacted, offer disabled employees the right to paid leave for employment assessment, rehabilitation or re-training.